(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This paper discusses the intricate dynamics of internal trade in Kashmir after the establishment of British Residency in 1885, focusing on the intersection of British colonial policies and ideologies, local economic practices, and sociopolitical structures. It examines how the colonial administrator’s professed commitment to laissez-faire ideology coexisted with paternalistic interventions, particularly in the grain trade—a vital sector in the subsistence economy of the region. The paper sheds light on the complexities of governance in Kashmir with the colonial officers alternating between advocating free trade and imposing regulatory frameworks that prioritized the ingraining of capitalistic values while enhancing welfare of the people. The study begins by contextualizing the economic policies implemented by the Dogra rulers under British suzerainty. It traces the evolution of laissez-faire ideology in the subcontinent and its selective application in Kashmir, where the grain trade became a key site of economic control and contestation. The research underscores how the British justified the abolition of state monopolization of market operations while simultaneously intervening during famines or grain shortages to mitigate political unrest and safeguard revenue streams. Through archival sources, official correspondence, and local accounts, this paper demonstrates the duality of British paternalism: on the one hand, measures like grain price controls, storage policies, and transportation improvements were framed as efforts to alleviate local suffering; on the other, these measures were often designed to maintain social stability and prevent disruptions. The paper also examines the role of local intermediaries, including traders and officials, in mediating the grain trade, and explores the social consequences of these trade dynamics, particularly their impact on rural communities and marginalized groups. By mapping fluctuations in grain availability and pricing the paper highlights the vulnerabilities faced by Kashmiri peasants under the system of grain trade.